A generic framework for multi-field two-phase flow based on the two-fluid model. (January 2017) - Liu, Y.; Talley, J.D.; Hogan, K.J.; Buchanan, J.R.
Abstract: Multiphase computational fluid dynamics (MCFD) simulation based on the two-fluid model has emerged as a valuable tool for a wide range of engineering applications. The classical two-field, two-fluid model treats each phase as a whole, which may introduce considerable uncertainties when a phase is comprised of significantly different forms, e.g., liquid droplets and liquid film, and/or vapor bubbles and continuous vapor core. This uncertainty becomes particularly important for resolving the multi-dimensional distribution of different fields in CFD applications. In relation to this, a multi-field model is necessary to mechanistically model a wide range of two-phase flow regimes. In this paper, a generic and rigorous multi-field two-fluid framework is derived based on the local instant formulation of the mass, momentum and energy conservation equations for single-phase fluids. The averaged field conservation equations and interfacial jump conditions are obtained from the local instantaneous formulation through a derivation with minimal assumptions. Based on this framework, a six-field two-fluid model is proposed as a practical model for typical two-phase flows in industrial systems, in which the flow regimes may span from bubbly to annular. These six fields include: continuous liquid, two dispersed liquid fields, continuous gas, and two dispersed gas fields. The field boundaries and different types of closure relations required to close the model are briefly discussed. The relationship between the momentum transfer terms in the Eulerian two-fluid model and the particle forces have been established by introducing a statistical averaging and the equation of motion for a single particle. Highlights: Generic averaging method proposed and applied to two-phase flow. A generalized multi-field two-fluid model derived from local instant formulation. Six-field classification proposed for all two-phase flow regimes. Connection established between Eulerian model and Lagrangian particle forces.